Recruitment to intellectual disability research: a qualitative study. (6th June 2012) - Nicholson, L.; Colyer, M.; Cooper, S.‐A.
Abstract Background Difficulties in the recruitment of adults with intellectual disability (ID) to research studies are well described but little studied. The aim of this study was to investigate the difficulties in recruiting to a specific research project, in order to inform future recruitment to ID research. Methods Individual semi‐structured interviews were held between September 2009 and May 2010 with people who had been involved as intermediaries in recruitment to the research project. These were transcribed verbatim and were independently analysed by two researchers using the Framework approach, who then agreed upon the key emerging themes. Results Ten interviews were analysed. A number of themes arose, including participant factors (interview anxiety, difficulties in understanding the concept of research, worry about negative feedback), the importance of the researcher (using a personal approach, meeting potential participants prior to recruitment) and motivators [enjoyment of the research interview (participant), obtaining a medical assessment (carer)]. The themes were then used to generate strategies to improve recruitment to ID research: these include the research team applying a more personal approach, developing the recruitment process to allow for multiple meetings with potential participants, and considering motivators for both participants and carers. Conclusions This study has used the experiences of intermediaries to identify strategies for improving recruitment to future ID research. This has implications in terms of both time and money. However, successful recruitment is essential to ID research, and we hope that the study will be used by ID researchers to review and improve their recruitment processes.